A Study On TESL Trainees’ Perceptions Towards Classroom Delivery Skills - Jaafar , Haliza; Tina Koh , Cheo Ling (2010)
This study examines the perceptions of TESL trainees in Universiti Teknologi Malaysia (UTM) towards classroom delivery skills. The focuses of this study include techniques of questioning and techniques of giving explanation and demonstration being employed during teaching practicum as well as the effects of these techniques towards students’ understanding. Data were collected from 50 TESL trainees from Faculty of Education, UTM. A set of questionnaire which consists of four parts was used as the instrument in this research. Besides questionnaires, seven trainees were interviewed to identify their perceptions of questioning, explanation and demonstration techniques. The result of this study shows that trainees are aware of the importance of these techniques and they had employed various strategies during their teaching practice. However, there are several aspects of questioning which trainees are still weak in. These aspects are sequence of questioning; habitual repetition of questions and students’ responses; asking too many questions at a time and the difficulty level of questions asked. On the other hand, trainees also show high level of awareness in terms of techniques of giving explanation and demonstration. 50 respondents had provided interesting introduction; used appropriate examples; showed positive teacher attitude as well as making sure presentations were visible and audible by students. Trainees’ perceptions on several aspects of explanation and demonstration are still in moderate level. These areas are informing learning goals to students; providing model and topic framework; encouraging peer learning in explanation as well as using concrete examples during explanation and demonstration. As a conclusion, trainees’ skills and techniques in questioning, explanation and demonstration can be improved in order to maximize the environment for effective learning and also to enhance students’ level of understanding.